Increasing control over biomineralization in conodont evolution - Shirley, Bryan; Leonhard, Isabella; Murdock, Duncan J.E.; Repetski, John; Świś, Przemysław; Bestmann, Michel; Trimby, Pat; Ohl, Markus; Plümper, Oliver; King, Helen E.; Jarochowska, Emilia (Nature Communications, 2024)
Vertebrates use the phosphate mineral apatite in their skeletons, which allowed them to develop tissues such as enamel, characterized by an outstanding combination of hardness and elasticity. It has been hypothesized that the evolution of the earliest vertebrate skeletal tissues, found in the teeth of the extinct group of conodonts, was driven by adaptation to dental function. We test this hypothesis quantitatively and demonstrate that the crystallographic order increased throughout the early evolution of conodont teeth in parallel with morphological adaptation to food processing. With the c-axes of apatite crystals oriented perpendicular to the functional feeding surfaces, the strongest resistance to uniaxial compressional stress is conferred along the long axes of denticles. Our results support increasing control over biomineralization in the first skeletonized vertebrates and allow us to test models of functional morphology and material properties across conodont dental diversity.
CRIS-Team Scopus Importer:2024-06-28